2022
DOI: 10.1002/jmd2.12313
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of Colombian experience with enzymatic screening in patients with features of mucopolysaccharidosis

Abstract: Mucopolysaccharidoses (MPSs) are a group of genetic alterations whose effect is the progressive intralysosomal accumulation of glycosaminoglycans. Affected individuals are deficient in one or more lysosomal enzymes which, depending on the MPS, may cause coarse facial features, short stature, multiple skeletal dysplasia, joint stiffness, or developmental delay. Their diagnosis is mostly performed late or incorrectly, and it represents a challenge since it requires specialized tests only performed in major citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Colombia —A 2019 law formalized an expansion of the national NBS program from CH to seven conditions and included EHDI and vision screening [ 1182 , 1183 , 1184 , 1185 ]. Efforts to continue expanding DBS screening have included developing MS/MS cutoff values and reviewing experiences and policy issues with MPS and other LSDs [ 1186 , 1187 , 1188 , 1189 ]. Continued interest in CCHD screening has included cost-effectiveness studies as well as a 14-site collaboration with the Nicklaus Children’s Hospital (Miami, Florida USA) [ 1190 , 1191 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colombia —A 2019 law formalized an expansion of the national NBS program from CH to seven conditions and included EHDI and vision screening [ 1182 , 1183 , 1184 , 1185 ]. Efforts to continue expanding DBS screening have included developing MS/MS cutoff values and reviewing experiences and policy issues with MPS and other LSDs [ 1186 , 1187 , 1188 , 1189 ]. Continued interest in CCHD screening has included cost-effectiveness studies as well as a 14-site collaboration with the Nicklaus Children’s Hospital (Miami, Florida USA) [ 1190 , 1191 ].…”
Section: Resultsmentioning
confidence: 99%
“…Colombia-A 2019 law formalized an expansion of the national NBS program from CH to seven conditions and included EHDI and vision screening [1182][1183][1184][1185]. Efforts to continue expanding DBS screening have included developing MS/MS cutoff values and reviewing experiences and policy issues with MPS and other LSDs [1186][1187][1188][1189].…”
mentioning
confidence: 99%
“…Conversely, MPS IIIB arises from gene variants in the N-acetylglucosaminidase ( NAGLU ) gene that leads mainly to neurodegeneration due to the lysosomal storage of heparan sulfate. In Colombia, MPS IVA stands as the most prevalent MPS subtype, with a combined prevalence of 1.98 and approximately 200 diagnosed patients 20 22 , while MPS IIIB ranks as the third most common, with 10.8% of the diagnosed patients and an estimated incidence of 0.36 affected individuals per 100,000 live births 22 . During the last few years, we have studied the cellular and molecular mechanisms of MPS IVA and MPS IIIB 17 , 23 , 24 , testing the potential of different therapeutic alternatives including recombinant enzymes 25 29 , gene therapy 30 34 , and pharmacological chaperones 35 37 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] For MPS IIIB, 256 mutations have been identified in the NAGLU gene, from which about 70 % are missense (The Human Gene Mutation Database, accessed February 2023, and [8][9] ). In Colombia, a recent report by Uribe-Ardila, et al [10] showed that MPS IIIB is the third more common MPS, with a 10.8 % of the MPS diagnosed patients and an estimated incidence of 0.36 affected individuals per 100,000 live births.…”
Section: Introductionmentioning
confidence: 99%